Thermoelastic Interaction in an Infinite Long Hollow Cylinder with Fractional Heat Conduction Equation (Advances in Applied Mathematics and Mechanics, 2018)
In this work, we introduce a mathematical model for the theory of generalizedthermoelasticity with fractional heat conduction equation. The presented modelwill be applied to an infinitely long hollow cylinder whose inner surface is tractionfree and subjected to a thermal and mechanical shocks, while the external surface istraction free and subjected to a constant heat flux. Some theories of thermoelasticitycan extracted as limited cases from our model. Laplace transform methods are utilizedto solve the problem and the inverse of the Laplace transform is done numericallyusing the Fourier expansion techniques. The results for the temperature, the thermalstresses and the displacement components are illustrated graphically for various valuesof fractional order parameter. Moreover, some particular cases of interest have alsobeen discussed.